Synthesis, Characterization and Crystal Structure of 2D Copper(II) Complex with 6-Ethoxy-4’,6’-dichloro-2,2’-[ethylenedioxybis(nitrilomethylidyne)]diphenol - Dong, W.-K.; Zhou, W.-M.; Zhang, X.-Y.; Zhao, M.-M.; Li, G.; Dong, X.-Y. (Asian Journal of Chemistry, 2014)
A new Cu(II) complex with asymmetric Salamo-type ligand, 6-ethoxy-4',6'-dichloro-2,2'-[ethylenedioxybis(nitrilomethylidyne)]diphenol (H2L) has been synthesized and characterized by elemental analyses, FT-IR, UV-visible spectra and single crystal X-ray crystallography. The X-ray crystal structure of the Cu(II) complex reveals it to be a mononuclear structure, which contains one Cu(II) atom and one deprotonated L2- unit. The center Cu(II) atom is tetra-coordinated, showing that the coordination sphere can be described as a square planar geometry distorted tetrahedrally by 33.07(4)º. In addition, the Cu(II) complex is linked to form an infinite 2D layer supramolecular structure through intermolecular C-H···O and C-H···Cl hydrogen bonds and p···p stacking interactions.